Pemberian Dukungan Gizi Puding Tepung Tempe Mempengaruhi Penyembuhan Luka Pasien Bedah - Fery Lusviana Widiany; Rochadi Rochadi; Susetyowati Susetyowati (JURNAL NUTRISIA, 2016)
Background : Malnutrition is common in hospitalized patients, particularly surgery, resulting in slowing the wound healing up to death. 34.7% malnourished patients who did not receive nutritional support are at risk of postoperative complications. Nutritional support can be given with tempeh flour pudding containing arginine and branched-chain amino acids. Objective : To investigate the effect of nutritional support in the form tempeh flour pudding on wound healing in surgical patients. Methods : This quasi-experimental study involve 152 elective surgery patients aged> 18 years. On the treatment group, the diet compliance is controlled, patient needs were adjusted after given tempeh flour pudding, whereas the control group were given hospital diet according to their needs. The independent variable is nutritional support, the dependent variable is wound healing. Data were analyzed by considering another variables, included ASA (American Society of Anesthesiologists Physical Status Classification) status. Results : Chi-square test the effect of nutritional support in the form tempeh flour pudding on wound healing showed p-value = 0.022, RR = 1.4. In multivariate test, ASA status has the most powerful effect on wound healing (B = 2.659, RR = 1.499, 95% CI = 1.142 - 1.969, p-value = 0.011). Conclusion : Nutritional support in the form tempeh flour pudding significantly effects on wound healing in surgical patients. Keywords : Nutritional support, tempeh flour pudding, wound healing, surgery patient.